2019
DOI: 10.1002/maco.201810666
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of atmospheric corrosion on mechanical properties with impact test: Carbon steel and Galvanized steel

Abstract: The present work presents the behavior of carbon steel and galvanized steel against atmospheric corrosion after 3 years of exposure at seven locations around the region of Valparaiso, Chile. Results show a relation between corrosion rates and environmental and meteorological conditions, categorized as CX for the Quintero zone, and C3 and C2 in the remaining six zones. Corrosion rate behaviors and material toughness losses were modeled using power functions and neural networks, found to be a function of environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[4,13,15,35] Results obtained from the current study are in agreement with the findings of other researchers. [3,4,6,36] 3.3 | Corrosion rates of galvanized steel and kinetic parameters Figure 3 shows the corrosion rates of galvanized steel observed from July 2018 to June 2019 at the urban, industrial, and marine test sites located in Karachi coastal city. It was observed that the corrosion rates decreased with the exposure time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,13,15,35] Results obtained from the current study are in agreement with the findings of other researchers. [3,4,6,36] 3.3 | Corrosion rates of galvanized steel and kinetic parameters Figure 3 shows the corrosion rates of galvanized steel observed from July 2018 to June 2019 at the urban, industrial, and marine test sites located in Karachi coastal city. It was observed that the corrosion rates decreased with the exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…SEM provides useful information about the morphology and structure of the corrosion products' layer. [14,15,[35][36][37] Figures 6 and 7 show the SEM images of the galvanized steel after 12 months of exposure at the urban, industrial, and marine test sites located in Karachi coastal city, and Table 3 demonstrates the morphologies of the corrosion products formed. For nearly all the test sites, these images illustrated that the corrosion products formed on galvanized steel were not compact and sometimes contained cracks.…”
Section: Scanning Electron Microscopy/ Energy-dispersive X-ray Specmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of rain varies in the range of 3.2-5.1 in extremely polluted industrial sites of Korea. [3][4][5] Under continuous exposure to an industrial environment, the galvanized lm of the insulator pin would be transformed into other atmospheric products rapidly. These corrosion rates would be faster enough to cover galvanized surfaces with corrosion byproducts in no more than 5-10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric corrosion is a complex process, highly sensitive to local environmental conditions. [1][2][3][4] The degree of metal deterioration and the type of corrosion product that forms on the surface of metals are directly related to the type of atmosphere it is exposed to, climatic factors, and pollutants. [5,6] Thus, any company making use of metal infrastructures exposed to different types of atmosphere-such as in the electrical sector-are aware of the impact of atmospheric corrosion.…”
Section: Introductionmentioning
confidence: 99%